Fieldwork and methodological problems in poverty research: A case study of a new village in Kedah / Lauw Swee Gim - Lauw, Swee Gim (1985)
Based on her experience in a new village, the researcher attempts to ‘unravel’' certain shortcoming of poverty research. The introductory chapter presents the definition and nature of poverty in Malaysia. In outlines the aims and limitations of the study. Method of research and sources of data are also mentioned here. Chapter Two contains the background characteristics of the New Village. Its history, demography, structure of administration, etc. Are described. The general patterns of employment, income and education among the respondents are tabulated. Chapter Three touches on the practical problem encountered in fieldwork. How the knowledge of the topic of study affects the spontaneity of the respondents, is discussed. Here subtlety in raising sensitive issues, is also emphasized. In Chapter Four, the researcher compares the reception and reaction of Malay and Chinese respondents during the study. Attempt are made to trace the reasons behind at time, the diverse responses of the respondents. Certain concepts related to poverty employed by past researchers and writers, are applied to substantiate the research findings in the concluding chapter. Among others, it reiterates the need to avoid insensitive framing of question as it might adversely affect the survey findings and conclusions drawn by researcher.